962 Prognostic Value of Neutrophil to Lymphocyte Ratio (NLR) and Platelet to Lymphocyte Ratio (PLR) for Small Renal Cell Carcinomas (RCC) After Image-Guided Cryoablation or Radio-Frequency Ablation (RFA). (19th August 2022) - Asif, A; Osman, F; Koe, JSE; Ng, A; Cartledge, J; Kimuli, M; Vasudev, N; Ralph, C; Jagdev, S; Bhattarai, S; Smith, J; Lenton, J; et al.
Abstract: Aim: This is the first study investigating the relationship between NLR or PLR and outcomes of percutaneous cryoablation or RFA for small RCCs with long-term outcomes. Method: All patients undergoing cryoablation or RFA for small RCCs (<7cm) from 2003–2016 at a regional centre for RCC were included. Optimal cut-offs for NLR/PLR were determined using the ROC curve and AUC using the Youden method. Outcomes were compared using Cox or logistic regression. Results: 203 patients (Cryoablation:103, RFA:100) were included. Median follow-up was 75 months and 98 months, respectively. Using the Youden method, high post-operative NLR values were associated with worsened local recurrence-free survival (LRFS) (NLR >5.38; HR: 5.13, p=0.037) and worsened Overall Survival (OS) (NLR >6.42; HR: 3.40, p<0.001) in all patients. High post-operative PLR values were associated with worsened OS in all patients (PLR >192; HR: 2.31, p=0.006) and RFA patients alone (n=100; PLR >260; HR: 8.27, p<0.001). Using continuous Cox regression model, greater changes in peri operative NLR were associated with worsened LRFS in cryoablation alone and all patients (Continous; HR: 1.09, p=0.028). Higher post-operative NLR was also associated with worsened LRFS in cryoablation patients alone (HR: 1.10, p=0.046). Post-operative NLR (HR:1.17, p=0.002), change in peri-operative NLR (HR:1.19, p=0.001), and change in peri-operative PLR (HR:1.20, p=0.009) were all associated with worsened CSS in all patients. Pre-operative PLR and NLR were not associated with complications and change in renal function. Conclusion: NLR and PLR are valuable prognostic factors for this group of patients and should be used to guide subsequent follow-up and monitoring of recurrence.